Social Support for Compliance in Consuming Iron Supplements in Adolescent Girls in Mamuju Regency, West Sulawesi, Indonesia - M, Mutmawardina.; Arsyad, Muhammad; Ibnu, Indra Fajarwati; Nasir, Sudirman; Hidayanty, Healthy (Journal of Neonatal Surgery, 2025)
Background:Compliance with iron-folic acid (IFA) tablet consumption among adolescent girls remains low despite the widespread distribution program. A lack of social support is one of the key factors influencing consumption behavior. Objective:To analyze the role of social support in shaping compliance with IFA tablet consumption among adolescent girls in Mamuju Regency, West Sulawesi. Methods:This study used a qualitative approach with a phenomenological design. Data were collected through in-depth interviews and focus group discussions (FGDs) with students, teachers, parents, and healthcare workers. Data analysis followed the Miles and Huberman approach. Results:Compliance among adolescent girls was influenced by perception, motivation, and types of social support. Teachers and healthcare workers provided informational, instrumental, and emotional support, while parents and peers offered mainly emotional support. Barriers included forgetfulness, unpleasant taste, parental restrictions, and side effects. Conclusion:Social support from various parties is crucial in increasing IFA tablet consumption compliance. Parental support is a key factor in the success of this intervention